Analisis Efektivitas Asesmen dan Tindak Lanjut Sekolah di SD IT Marhamah Kabupaten Solok Selatan - Yelly Martaliza; Syovia Lolita; Rezki Putra; Vilmaisari; Husni Nofrita; Fitri Sari Angkat; Hafiz Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In the context of implementing the Merdeka Curriculum, this study attempts to assess the efficacy of evaluation and follow-up procedures at SD IT Marhamah, an integrated Islamic elementary school in South Solok Regency. A descriptive qualitative method is used in this study. The principal and three teachers were interviewed in-depth, classroom observations were made, and assessment instrument records were examined in order to gather data. Twelve students served as research subjects. The Miles and Huberman model was used for data analysis. The results show that while assessments (diagnostic, formative, and summative) have been administered in accordance with the principles of the Merdeka Curriculum, there are still differences in the caliber of the instruments and the uniformity with which teachers apply the rubric. Remedial, enrichment, and character-building follow-ups have been conducted, but their documentation is still not organized. While time limits, differences in teachers' IT proficiency, and the lack of consistent rubrics are challenges, the principal's leadership and teacher collaboration are the primary supportive aspects. The conclusion is that while the school's assessment and follow-up procedures are rather successful, they are still not at their best. To guarantee long-term improvements in learning quality, it is necessary to strengthen the technical aspects of instrument creation, increase teacher proficiency in assessment analysis, and create a systematic follow-up documentation system.